DYNAMIC YARD TEMPLATE DESIGN TO IMPROVE UTILIZATION AND OPERATION EFFICIENCY ON VERTICAL LAYOUT-CONTAINER YARDS CONSIDERING UNCERTAINTY OF TRUCK ARRIVAL - Nurminarsih, Siti; Putri, Maulin Masyito; Rusdiansyah, Ahmad (JEMIS (Journal of Engineering & Management in Industrial System), 2018)
Loading containers into a vessel can be delayed because of inefficient processes in the container yard. These container yard inefficient processes can be caused by inappropriate stacking position and inefficient crane operation. Inappropriate containers stacking positions may need some preparatory jobs of rearranging containers ahead of loading time to reduce delays in the process. The method will allow preparatory jobs to be scheduled together with main jobs to optimize use of the idle time of ASCs. This research aims to find a better scheduling strategy of twin ASCs as well as improving land utilization in a vertical-layout container yard to minimize delays in containers loading process. The uncertainty of truck arrival is accomodated by implementing iterative rescheduling in look-ahead planning horizon. The algorithm finds the optimal position of the container in the yard by implementing scoring function for each available slot. Finally, some numerical experiments are conducted to prove the performance of the algorithm.